Gene Deletion Mutants Reveal a Role for Semaphorin Receptors of the Plexin-B Family in Mechanisms Underlying Corticogenesis - Hirschberg, Alexandra; Deng, Suhua; Korostylev, Alexander; Paldy, Eszter; Costa, M. R.; Worzfeld, Thomas; Vodrazka, Peter; Wizenmann, A.; Götz, M.; Offermanns, Stefan; Kuner, Ruprecht (Molecular and cellular biology, 2010)
Semaphorins and their receptors, plexins, are emerging as key regulators of various aspects of neural and nonneural development. Semaphorin 4D (Sema4D) and B-type plexins demonstrate distinct expression patterns over critical time windows during the development of the murine neocortex. Here, analysis of mice genetically lacking plexin-B1 or plexin-B2 revealed the significance of Sema4D-plexin-B signaling in cortical development. Deficiency of plexin-B2 resulted in abnormal cortical layering and defective migration and differentiation of several subtypes of cortical neurons, including Cajal-Retzius cells, GABAergic interneurons, and principal cells in vivo. In contrast, a lack of plexin-B1 did not impact on cortical development in vivo. In various ex vivo assays on embryonic forebrain, Sema4D enhanced the radial and tangential migration of developing neurons in a plexin-B2-dependent manner. These results suggest that Sema4D-plexin-B2 interactions regulate mechanisms underlying cell specification, differentiation, and migration during corticogenesis.